Penerapan Pendekatan Gamifikasi Siswa Kelas XII di SMK PGRI 3 Blitar pada Materi Permutasi dan Kombinasi - Rahayu, Meike Nanda Wahyu Putri; Riki Suliana R.S; Suryanti (Papanda, 2025)
Education plays an important role in shaping character, developing potential, and preparing students to face future challenges. Lack of appreciation for student learning outcomes is a significant issue that can negatively impact student learning motivation. This study aims to determine the application of gamification to the Permutation and Combination material implemented at SMK PGRI 3 Blitar. The method used is Classroom Action Research (CAR) by adopting the Arikunto cycle which refers to the basic model of Kurt Lewin. The research subjects were 22 students from grade XII consisting of 7 boys and 15 girls. The research sample was taken from students in one class recommended by the mathematics subject teacher based on the consideration that the class was considered representative of the characteristics and in accordance with the research needs. The application of the gamification approach was carried out according to the procedures of the Problem Based Learning (PBL) learning model. Data collection instruments and techniques were carried out through tests and observations. Tests were used to measure the level of students' conceptual understanding of the permutation and combination material, while observations were carried out to monitor learning activities, student engagement, and their responses during the learning process. The results of the study showed that the final cycle test had achieved classical completeness with a completeness percentage of 81.81% and the results of observations of teacher and student activities at each meeting were in the very good criteria.